Carcinoma hepatocelular apresentado por metástase óssea - Torres,Orlando Jorge Martins (2000)
Patients with hepatocellular carcinoma usually present with signs of liver disease, but bone metastasis at the initial presentation is a rare condition. We report a case of bone metastasis at the initial presentation in a patient with hepatocellular carcinoma. A 39 years old man complained of abdominal pain, fever, and weight loss. Computed tomography revealed osteolytic lesions in the body of the lumbar vertebra. Histological examination of the liver showed to be hepatocellular carcinoma. The authors believe that hepatocellular carcinoma should be included in the protocols in patients with clinical manifestations of bone disease.